Convergence theorem for equilibrium problem and Bregman strongly nonexpansive mappings in Banach spaces. (1st February 2016) - Kumam, Wiyada; Witthayarat, Uamporn; Kumam, Poom; Suantai, Suthep; Wattanawitoon, Kriengsak
Abstract : In this paper, we present an iterative scheme for Bregman strongly nonexpansive mappings in the framework of Banach spaces. Furthermore, we prove the strong convergence theorem for finding common fixed points with the set of solutions of an equilibrium problem.